Digital Humanities? Gibt’s doch gar nicht! - Patrick Sahle (Zeitschrift für digitale Geisteswissenschaften, 2015)
The Digital Humanities are either a field of research or an academic discipline, possibly both. In any case, they are embedded in an extensive infrastructure in regard to organization, information, and communication and build upon long traditions in various areas of research. Furthermore, as a link between the humanities and computer science, the field seems to be highly attractive, not only to these areas, but also to neighboring disciplines as well as to the research funding agencies. Outside of the academic context, the mass media have discovered the digital humanities in recent years. While this attractiveness has several positive integrative effects, the current DH hype is not without certain risks, ranging from the mere misappropriation of the term to explicitly defensive or negative attitudes, and even ignorance and denial: DH? But there is no such thing!